Effect of Fine Sanctions on Taxpayers' Compliance in Paying Land and Building Tax in South Tondano District Minahasa Regency - Anita Nisa Kambey; Ratna Taliupan; Friska Langelo; Edino Ayub Lomban; Regina Beatrix Takakobi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This research aims to determine how much fines affect taxpayer compliance in paying land and building taxes in South Tondano District, Minahasa Regency. Fines are an important instrument to encourage taxpayer compliance, where late PBB payments are subject to an administrative fine of 2% per month with a maximum fine of 48% or the equivalent of 2 years. The research method used is quantitative, with primary data as the source. The population in this research is all taxpayers in South Tondano District, Minahasa Regency, namely 771 taxpayers who are a sample of 50 taxpayers. Data analysis uses a regression test to test the effect of the fine sanction variable on taxpayer compliance in paying PBB. The research results show that results show that fines have a positive and significant effect on taxpayer compliance in paying PBB. These findings indicate that the higher the administrative fine imposed, the higher the level of taxpayer compliance because taxpayers will choose to pay taxes on time rather than being late and subject to fines. This research concludes that applying fines has effectively increased taxpayer compliance in paying PBB. Therefore, enforcement of fines needs to be carried out consistently to ensure a higher level of taxpayer compliance.